2011
DOI: 10.1029/2010jd014608
|View full text |Cite
|
Sign up to set email alerts
|

Aura Microwave Limb Sounder observations of the polar middle atmosphere: Dynamics and transport of CO and H2O

Abstract: [1] The vertical structure and evolution of the wintertime annular modes are studied using 6 years of geopotential height, carbon monoxide (CO), and water vapor (H 2 O) data from Aura Microwave Limb Sounder. The Northern Hemisphere annular mode (NAM) and the Southern Hemisphere annular mode (SAM) reveal a strong coupling of the dynamics in the stratosphere and mesosphere between 316 hPa (∼9 km) and 0.002 hPa (∼90 km). CO is a good tracer throughout the middle atmosphere, while variable vertical gradients of H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 64 publications
5
71
1
Order By: Relevance
“…These are the years of strong sudden stratospheric warming (SSW) events (Lee et al, 2009). Lee et al (2011) observed enhanced planetary wave activities during the SSW events from Aura MLS observations, and they believe the planetary waves serve as an efficient filter to prevent upward propagation of GWs. More explanations can be found in Dunkerton and Butchart (1984).…”
Section: Temporal Variationsmentioning
confidence: 99%
“…These are the years of strong sudden stratospheric warming (SSW) events (Lee et al, 2009). Lee et al (2011) observed enhanced planetary wave activities during the SSW events from Aura MLS observations, and they believe the planetary waves serve as an efficient filter to prevent upward propagation of GWs. More explanations can be found in Dunkerton and Butchart (1984).…”
Section: Temporal Variationsmentioning
confidence: 99%
“…H 2 O is a good tracer in the mesosphere and the stratosphere, because the subsidence inside the vortex in combination with vertical H 2 O gradients leads to different H 2 O mixing ratios inside and outside of the vortex (e.g. Lee et al, 2011, and references therein). H 2 O cannot be used as a tracer in the altitude region of the H 2 O volume mixing ratio (VMR) peak.…”
Section: The Edge Of the Polar Vortexmentioning
confidence: 99%
“…in the course of stratospheric sudden warmings. Around the stratopause H 2 O is not a good tracer due to its local maximum in the upper stratosphere (Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Using observations of Aura/MLS and Empirical Orthogonal Function analysis Lee et al (2011) There have been previous studies using data of ground based microwave radiometers to investigate the stratospheric and mesospheric response to SSWs. Seele and Hartogh (2000) demonstrated that ground based measurements of mesospheric water vapor can be used to monitor transport processes during dynamical events such as SSWs.…”
Section: Introductionmentioning
confidence: 99%